2020
DOI: 10.1007/s12155-020-10205-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental-Economic Assessment of the Pressure Swing Adsorption Biogas Upgrading Technology

Abstract: A large-scale biogas upgrading plant using the CarboTech® technology with a treatment capacity of 1333 Nm3 biogas per hour was analyzed. Our scope of evaluation encompasses all technology steps that are necessary for upgrading biogas, i.e., both pretreatment and biogas upgrade. A cradle-to-gate life-cycle and life-cycle cost assessment (LCA and LCCA) methodology was used with the functional unit (FU) of 1 Nm3 of biogas upgraded in order to ease comparison with other biogas upgrading technologies. The calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 14 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…First, all 23 articles were classified according to their research field in order to limit the analysis to the field of energy. Thus, 14 articles with reference to the energy sector could be identified, of which the authors focused on the prospective LCSA of propulsion systems for vehicles in 8 [11][12][13][14][15][16][17][18] and on fuels/energy carriers in 2 articles [19,20]. 4 studies dealt with the assessment of energy systems, 3 of which refer to countries like Spain or UK [21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, all 23 articles were classified according to their research field in order to limit the analysis to the field of energy. Thus, 14 articles with reference to the energy sector could be identified, of which the authors focused on the prospective LCSA of propulsion systems for vehicles in 8 [11][12][13][14][15][16][17][18] and on fuels/energy carriers in 2 articles [19,20]. 4 studies dealt with the assessment of energy systems, 3 of which refer to countries like Spain or UK [21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Stamford & Azapagic 2014 extrapolated injury rates to the future based on historical trends ( [24] p. 202). Moreover, we observed that some of the authors (5 articles) came up with own assumptions without citing sources or methods [11,14,17,18,20]. For instance, Onat et al considered two battery charging scenarios related to the electricity mix in their studies; in scenario 1 the electricity mix was based on the existing electricity infrastructure, in scenario 2 on solar power [17,18].…”
Section: Prospective Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all the parameters affecting the overall energy efficiency of the complete biogas upgrading process, the loss of CH 4 is the most significant. The pressure swing adsorption process has a slightly lower energy consumption than water scrubbing (WS) but consumes much more energy than the chemical adsorption process (Kohlheb et al 2020). The energy consumption required by the chemical adsorption process is about 15% less than the water scrubbing process (Vilardi et al 2020).…”
Section: Techno-economic Analysis Of Biogas Upgrading Technologiesmentioning
confidence: 99%